(untitled) (Journal of Human Sciences, 2020)
This research aims to study the issue of the spatial disparity of land transport services in the city of Sebha, according to a purely geographical perspective that focuses mainly on the issue of the reality of these services and their efficiency, and the problems they face in order to provide a good service to the city’s residents and its regional surroundings, where land transport services are distinguished. Being of a regional dimension that exceeds the borders of Sebha. The importance of land transport services in the city of Sebha is also evident by the fact that it is the only burden on which to provide transport services to the city’s residents and others, as there are no other types of transport in the city that reduce the load or constitute competition even for land transportation, so the city’s airport He remained suspended from service until the last moments, before the completion of this research .Also, the lack of maritime transport services due to it being an inner city located in the middle of the desert, hence the importance of this study, which focuses on three basic places to evaluate the movement and efficiency of transport in Sebha, represented by its three land entrances, namely: the northern entrance - the northeast entrance - the southeast entrance .This evaluation is based on a study of the density and traffic composition of the various road transport vehicles, including cars, buses, small and large trucks, and others that enter and exit daily from these entrances. By comparing the field data of the traffic flow with these entrances separately, and comparing them with each other, it is possible to determine the places of strength and weakness in the transport movement, its intensity and traffic structure. By analyzing the reasons for that weakness or spatial strength, an integrated picture of the spatial disparity of road transport services in the city of Sebha can be drawn, using some interviews with drivers of different means of transport that used these traffic gates during the field data collection period for this study.